On the optimal renewal of bilinear functionals in linear Normed spaces - Babenko, V. F.; Rudenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study the problem of optimal renewal of bilinear functionals on the basis of optimal linear information in the general statement. We also represent some new results for special spaces of functions.